Seed micromorphology of tribe Desmodieae (subfamily Papilionoideae, family Leguminosae) from Thailand with its taxonomic implications - WITSANU SAISORN; SOMRAN SUDDEE (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saisorn W, Suddee S. 2023. Seed micromorphology of tribe Desmodieae (subfamily Papilionoideae, family Leguminosae) from Thailand with its taxonomic implications. Biodiversitas 24: 5572-5585. The seed micromorphology of 21 genera and 58 species of the tribe Desmodieae in Thailand was studied. The result showed that the shape of the seed can be ellipsoid or transversely ellipsoid, irregular, oblongoid, quadrangular, rectangular, reniform, rhomboid, subcircular, and triangular. An oblongoid shape is restricted to the genus Sohmaea; the seeds’ length, width, and thickness are 0.94-5.93 mm, 0.78-3.65 mm, and 0.39-1.92 mm, respectively. The testa color can be light green to green, yellow, light to dark brown, or black. Testa patterns can be classified into nine types: colliculate, colliculate-rugulate, fissured, pitted, reticulate, reticulate-reticulate, reticulate-rugulate, rugulate, and smooth. The rim-arillate aril can be thin, thick, or well-developed. This tribe is classified into three groups based on aril types. Group I: a thin rim-arillate type is restricted to Akschindlium godefroyanum. Group II: a thick rim-arillate type is found on the seeds of the most studied plants. Group III: a well-developed rim-arillate type is a taxonomic characteristic of Codariocalyx. The overall shape of the rim-arillate aril is subcircular, circular, subcircular-elliptic, elliptic, elliptic-oblong, and oblong. An oblong shape of the rim-arillate aril is a unique character for Grona heterophylla compared to other species within Grona.